Cost-effectiveness analysis of tyrosine kinase inhibitors (erlotinib vs. gefitinib vs. afatinib) in non-small-cell lung cancer - Fitri Nurhayati, Yusi Anggriani, Elisna Syahruddin, Hesty Utami Ramadaniati, Tri Kusumaeni (Journal of Applied Pharmaceutical Science, 2021)
Tyrosine kinase inhibitors (TKIs; e.g., erlotinib, gefitinib, and afatinib) are the first-line therapy for non-small-cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) (+) common mutation. The study’s objective was to analyze the cost-effectiveness of erlotinib, gefitinib, and afatinib in NSCLC patients. The subjects of the study were NSCLC patients with EGFR (+) mutation receiving either erlotinib, gefitinib, or afatinib from January 2017 to December 2019. The exclusion criteria were patients receiving the respective therapy for less than 2 months and patients unable to complete the treatment until after December 2019. The parameter of treatment effectiveness was progression-free survival (PFS), which was measured as the time from initiation of the therapy until disease progression occurred or a patient became deceased. Direct medical costs, from the hospital perspective, were calculated during the treatment. A nonparametric Kruskal–Wallis test was conducted to compare the median PFS and direct medical cost between the three treatment groups. The median PFS of patients receiving erlotinib, gefitinib, and afatinib was 8 months, 12 months, and 5 months, respectively. There were significant differences in the monthly direct medical costs between the study groups: erlotinib (IDR 13,545,116), gefitinib (IDR 14,727,887), and afatinib (IDR 12,146,834). The cost-effectiveness ratio of the study groups was as follows: erlotinib IDR 1,693,139.50/months; gefitinib IDR 1,227,323.92/months; and afatinib IDR 2,429,366.80/months. Gefitinib was the most cost-effective TKI, followed by erlotinib and afatinib.
Keywords: Cost-effectiveness, erlotinib, gefitinib, afatinib, non-smallcell lung cancer.